2022
DOI: 10.1038/s41598-022-21940-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fatigue on electromechanical response times in basketball players with and without persistent low back pain

Abstract: Typically, athletes alter movement mechanics in the presence of back pain, but the effect of these changes on lower extremity injury risk is not well understood. This study aimed to compare the effect of fatigue on electromechanical response times during a choice reaction task in basketball players with and without persistent low back pain. Twenty-four male basketball players participated. Total reaction time (TRT), premotor time (PMT), and electromechanical delay (EMD data were recorded before and after fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…A study conducted by Abdollahi et al demonstrated that basketball players with cLBP have prolonged EMD in gastrocnemius and tibialis anterior muscles and shortened EMD of semitendinosus, vastus lateralis, and vastus medialis oblique muscles after lower limb muscle fatigue than healthy basketball players [18]. Another study conducted by Le Mansec et al found that EMD of the biceps brachii in healthy individuals would be increased after muscle fatigue induced by intermittent contractions of biceps brachii [20].…”
Section: Muscle Fatigue and Reaction Time Previous Studies Havementioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Abdollahi et al demonstrated that basketball players with cLBP have prolonged EMD in gastrocnemius and tibialis anterior muscles and shortened EMD of semitendinosus, vastus lateralis, and vastus medialis oblique muscles after lower limb muscle fatigue than healthy basketball players [18]. Another study conducted by Le Mansec et al found that EMD of the biceps brachii in healthy individuals would be increased after muscle fatigue induced by intermittent contractions of biceps brachii [20].…”
Section: Muscle Fatigue and Reaction Time Previous Studies Havementioning
confidence: 99%
“…Te PMT contains cognitive components, while EMD indicates pure electromechanical delay [60,61]. However, the efect of muscle fatigue on the reaction time of limb movements in cLBP was reported seldomly [18]. To address this issue, this study explored the potential relationship between muscle fatigue and reaction time through the arm-raising task with visual cues prior to and following exercise-induced muscle fatigue in patients with cLBP and quantifed the weight of PMT and EMD in TRT.…”
Section: Muscle Fatigue and Reaction Time Previous Studies Havementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, some previous similar studies have yielded different results. For example, Sajjad Abdollah et al's [19] study revealed that the EMD of lower limb muscles (gastrocnemius, tibialis anterior, and semitendinosus) in basketball players with cLBP had changed through inducing lower limb muscle fatigue. Furthermore, another study performed intermittent isometric knee exions at 60% of the maximum voluntary contraction until failure, and demonstrated that fatigue training resulted in shorter EMD of knee muscles (biceps femoris, semitendinosus, etc.)…”
Section: Muscle Fatigue and Reaction Timementioning
confidence: 99%
“…Studying these phases separately can help clarify the speci c process of neuromuscular reaction in response to the various stimuli of different circumstances, which is applicable to muscle fatigue and chronic pain research. For instance, a prior investigation has demonstrated that athletes with cLBP required longer PMT and TRT to adapt fatigue when performing a choice reaction time task, in contrast to healthy athletes [19]. Another study examining the effects of fatigue on patellar tendon re ex responses in males and females also found that the TRT(especially in EMD period ) was signi cantly increased in females after fatigue but not in males [20].…”
Section: Introductionmentioning
confidence: 97%